Investigating the origins of contemporary basics on the drum kit: an exploration of the role of the hi-hat in Anglo-American popular musics from 1960 until 1974. Issue 2 (8th April 2014) - Fleet, Paul; Winter, Jonathon
Abstract The hi-hat is an instrument within the kit that is often the driving force of numerous grooves, and how the playing of this instrument developed across the period 1960–1974 in Anglo-American popular musics is a useful guide when considering how the drum kit has in turn defined certain genres and styles. This paper will study a selection of grooves that use the hi-hat as a discriminating factor which will help trace the origin of certain basics within straight rhythms. The first iterations of these grooves are traced and analysed to uncover the origin of particular patterns that have since become accepted and well used within popular musics. This date period is a particularly rich seam of popular music history in this respect, beginning with the earliest recorded examples of particular hi-hat techniques and leading to what could be considered a period where these techniques became commonplace.